Recent advances in the development of the physically crosslinked hydrogels and their biomedical applications (Research, Society and Development, 2023)
Hydrogels are three-dimensional networks formulated from natural or synthetic polymers with a high capacity to absorb and transport water in their structure. Hydrogels are prepared from the crosslinking of their polymeric chains, which involves two basic mechanisms: chemical crosslinking and physical crosslinking. In chemical crosslinking, hydrogels are held together by covalent bonds; while physically cross-linked hydrogels are produced by non-covalent interactions, such as hydrogen bonds, electrostatic interactions, and hydrophobic forces, among others. Physically cross-linked hydrogels are more similar to biological systems due to their assembly dynamics, so they have wide biomedical applications. The most used approaches in the preparation of hydrogels by physical crosslinking include freeze-thaw, formation of stereocomplexes, ionic interaction, hydrogen bonding, crystallization, and crosslinking by hydrophobic interactions. These approaches are briefly discussed in this review. Some biomedical applications of these hydrogels will also be discussed.